USE OF VERTICAL ELECTRICAL SOUNDINGS TO DELINEATE SEAWATER INTRUSION IN A COASTAL AREA OF BYUNSAN, KOREA - Song S.; Lee J.; Park N. (My University, 2007)
To delineate spatial extent of seawater intrusion in a small experimental watershed in the coastal area of Byunsan, Korea, electrical resistivity surveys with some evaluation core drillings and chemical analysis of groundwaters were conducted. The vertical electrical sounding (VES) method was applied, which is useful to identify variations in electrical characteristics of layered aquifers. The drilling logs identified a three-layered subsurface including reclamation soil, weathered layer and relatively fresh sedimentary bedrock. The upper two layers are the main water-bearing units in this area. A total of 30 electrical sounding curves corresponded mostly to the H type and they were further divided into three classes: highly conductive, intermediate, and low conductive, according to the observed resistivity values of the most conductive weathered layer. In addition, groundwater samples from 15 shallow monitoring wells were analyzed and thus grouped into two types based on HCO3/Cl and Ca/Na molar ratios with TDS levels, which differentiated groundwaters affected by seawater intrusion from those not or less affected. According to relationships between the three classes of the sounding curves and groundwater chemistry, locations of the monitoring wells with low HCO3/Cl and Ca/Na ionic ratios coincided with the area showing the highly conductive type curve, while those with the high ratios corresponded to the area showing low conductive curve type. Both the low electrical resistivity and the low ionic ratios indicated effects of seawater intrusion. From this study, it was demonstrated that the VES would be useful to delineate seawater intrusion in coastal areas.
Keywords: SEAWATER INTRUSION; VERTICAL ELECTRIC SOUNDING; RESISTIVITY; IONIC RATIO; KOREA